2022
DOI: 10.1007/978-3-030-95630-1_6
|View full text |Cite
|
Sign up to set email alerts
|

FEDGEN Testbed: A Federated Genomics Private Cloud Infrastructure for Precision Medicine and Artificial Intelligence Research

Abstract: The cloud computing space is enjoying a renaissance. Not long ago, cloud computing was confined to the wall of high-revenue companies, but in recent times a growing number of businesses, public and private institutions are turning to the cloud computing platform to reap the benefits of a self-service, scalable, and flexible infrastructure. Moreover, with the increased implementation, advantages, and popularity of artificial intelligence, the demand for computing environments to solve age-old problems such as m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…CApIC-ACE seeks to develop new diagnostic biomarkers for prostate and breast cancers. They are also building a federated genomics (FEDGEN) infrastructure customized to process and analyze indigenous genomic data ( Adetiba, E. et al, 2022 ). The MRC/UVRI and LSHTM Uganda Research Unit is promoting the genetic epidemiology of both communicable and non-communicable diseases (NCDs) in Uganda.…”
Section: Challenges In the Application Of Personalized Medicine In Af...mentioning
confidence: 99%
See 1 more Smart Citation
“…CApIC-ACE seeks to develop new diagnostic biomarkers for prostate and breast cancers. They are also building a federated genomics (FEDGEN) infrastructure customized to process and analyze indigenous genomic data ( Adetiba, E. et al, 2022 ). The MRC/UVRI and LSHTM Uganda Research Unit is promoting the genetic epidemiology of both communicable and non-communicable diseases (NCDs) in Uganda.…”
Section: Challenges In the Application Of Personalized Medicine In Af...mentioning
confidence: 99%
“…The study's findings reported that aspirin could be considered as a good preventive agent for colorectal cancer in group of pateints with Lynch syndrome. In 2022, Mathers et al (2022 subjected participants with Lynch syndrome to a randomized doubleblind treatment with 30 g resistant starch (RS) (n = 463) daily or placebo (n = 455) for up to 4 years. Upon following up with the participant for up to 20 years, they concluded that 30 g daily RS confers substantial protection against non-colorectal cancers for the group of patients with Lynch syndrome.…”
Section: The Current State Of Personalized Medicine In Africamentioning
confidence: 99%
“…The FEDGEN testbed [58] makes use of a Broker to manage resource negotiations between end-users and CSPs within the federated cloud environment. The testbed is built with Open-Stack middleware.…”
Section: A the Fedgen Testbedmentioning
confidence: 99%